Effect of Different Breeds of on Growth performance of Pure Breed and Cross Breed Chicks - khaminsou, viphone; KEOMOUNKHOUN, Bamphen (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This experiment was conducted at Lak 13 Agriculture Lab Centre, Champasack University in 6 months. The objective is to compare egg production, mortality rate and live ability of pure breed and cross breed. To compare the growth performance of pure and cross breed chicks. Factorial in Randomized Complete Block Design (RCBD) was used for this experiment; there are 9 treatments and three replications. Three chicken breeds were selected for experiment including native, Rhode Island Red, and Barred Plymouth Rock which be healthy, average weight 1.8 – 2 Kg and aged 22-24 weeks. Results of the experiment showed that there was statistical significance (P<0.05) of egg production. The highest egg production was T1 (Rhode Island Red x Rhode Island Red) with 37 eggs/head, while lowest egg production was T9 (Native x Native) with 17 eggs/head. There was no statistical significance on percentage of pertilized egg (P>0.05). There was not statistically significant (P>0.05) of among of healthy chicks, the highest among of healthy chicks was T2 with 24.83 chicks/head, while the lowest among of healthy chicks was T9 with 11.33 chicks/head. However, there was not statistically significant (P>0.05) of average daily gain (ADG), and feed conversion ratio (FCR) of pure breed and cross breed. Conclusion of this experiment was cross breeding between Rhode Island Red cocks and Barred Plymouth Rock hens reched the best production, especially egg production and healthy chicks. Therefore, these findings provide useful information for improving layer breeding programs in Laos.